KELAIKAN BANGUNAN FASILITAS UMUM UNTUK TEMPAT EVAKUASI TSUNAMI DI KECAMATAN BAITUSSALAM - Yunita Idris; Dian Tri Andani Saputra; Syamsidik Syamsidik (Prodi Magister Teknik Sipil Unsyiah, 2021)
Tsunami evacuation buildings in the tsunami-prone zone area are essential to minimize the number of fatalities. The purpose of this study is to analyze the behavior of the existing building structures caused by earthquake and tsunami loads in the Baitussalam District. The existing buildings that were reviewed were the SD 1 Lambada Klieng Building and the Syahamah Aceh Putra Foundation Building. The methodology in determining the capacity of the existing structures by conducting a field assessment to obtain data on existing buildings which will then be modeled, both existing buildings and a potential design of buildings using structural analysis software. for analysis. The results of the analysis show that the existing buildings need to be strengthened and redesigned to be able to withstand the effects of earthquake and tsunami loads. The remodeled of the buildings included modifying the column dimensions and also additional building stories. The remodeled of the existing building structures to become the tsunami evacuation structures is safe enough against earthquake loads and tsunami loads that occur.